Gender Differences in Cardiac Autonomic Modulations as Reflected by Heart Rate Variability - Ghazala Jawwa, Humaira Fayyaz Khan, Mehwish Iftikhar, Amna Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Heart rate variability is the most important noninvasive tool to quantify cardiac autonomic function. Aim: To compare the “frequency domain” parameters of “heart rate variability” in male and female subjects. Study Design: Cross-sectional study. Methodology: Present study was carried out at Islamic International Medical College and Yusra medical and dental college from June 2014 to December 2018. Four hundred subjects from both the genders between 20-40 years of age were included in the study after filling written informed consent. Ten minutes ECG of the subject was taken using power lab and explored for heart rate variability observing the protocols of “Task Force of European Society of Cardiology and the North American Society of Pacing Electrophysiology Frequency domain indices of heart rate variability obtained using “fast Fourier transform” .and were compared among male female groups. Results: Male subjects have considerably low high frequency in absolute unit and normalized unit (p≤ 0.05)and high low frequency in normalized unit and absolute unit (p ≤ 0.05 and .001 respectively)and low to high frequency ratio when compared with females(p ≤0.001). Conclusion: We concluded that assessment of Heart rate variability is an important measure of autonomic nervous system. Males exhibit reduced HRV parameters as compared to females showing that female have good vagal control than males.